Guidelines for the Instructional Supervision of Teachers in Thai Language Departments in Secondary Schools under the Secondary Educational Service Area Office 4 - Kryyasit, Kantimam; Thanompongchart, Phasphan; Sudrung, Jurairat (An Online Journal of Education, 2021)
The purposes of this study were: 1) To study the current state and expectations for the instructional supervision of teachers in Thai language departments at secondary schools under the Secondary Educational Service Area Office 4; and 2) To propose guidelines for the instructional supervision of secondary school teachers in Thai language departments. The population was 329 respondents and 9 interviewees. A 5-point Likert scale questionnaire and semi-structured interviews were used as research instruments. Regarding the current state of instructional supervision of teachers in Thai language department, the findings showed that the area with the highest average was classroom management. Regarding the teachers’ expectations for instructional supervision, the area with the highest average was teaching and learning management. The PNImodified results suggested that a learning measurement and evaluation aspect were most needed. The guidelines for instructional supervision of teachers in Thai language departments can be divided into 4 aspects, namely, the curriculum, classroom management, teaching materials, and class evaluation.